Integrated Optical Filter Using Spiral-Based Cascaded Mach–Zehnder Interferometers - Zhiqiang Ge; Chao Zeng; Yongkang Gong; Lingxuan Zhang; Guoxi Wang; Leiran Wang; Qibing Sun; Jinhai Si; Wei Zhao; Wenfu Zhang (IEEE Photonics Journal)
We have proposed a new compact integrated optical filter based on cascaded Mach-Zehnder interferometers (MZIs), and designed corresponding coupling structures without S-bend. The wavelength dependence and fabrication tolerance of coupling structures constructed in straight waveguides and bent waveguides were sufficiently analyzed by the finite-difference time-domain (FDTD) method. The results showed that the curved coupler possesses property of broadband with large fabrication tolerance. Specifically, for the presented 3 dB coupler incorporated with the asymmetric curved waveguides, the deviation of transmission remained below 2% at wavelength from 1.5 to 1.6 μm, which is greatly helpful to broadband spectral response of cascaded MZIs. By connecting curved couplers with spiral waveguides, a filter by means of two-stages cascaded MZIs was optimally demonstrated to realize a channel spacing of 10 nm. The spiral-based MZIs filter (SBMF) provides a new reference for MZIs filter limited by footprint and wavelength dependence.